The analysis and conservation of a 5th century CE child's tunic from Egypt - Margariti, Chistina; Berghe, Ina Vanden; Sava, Gabriela; Chanialaki, Tina (Archaeological Textiles Review, 2020)
This paper presents the conservation and analysis of an excavated child’s linen tunic originating from Egypt, which was donated to a museum in the late 19th century. The tunic had repeatedly treated and alteratered during its museum life, starting as early as the 1930s when it was wet cleaned, and later in the 1970s, when it received an adhesive support. It was probably during this treatment that it lost its three-dimensional shape. In 2015, the tunic was conserved as part of an EU co-funded refurbishment of the museum to which it belongs. During this conservation, the tunic was returned to its original three-dimensional shape, the purple dye used to decorate it was identified as a mixture of madder and indigoid, and it was also dated between the fifth and seventh centuries CE using radiocarbon 14 dating techniques.